Why policies on trade and markets matter during the Nutrition Decade - Díaz-Bonilla, Eugenio; Hepburn, Jonathan (2017)
On 25 September 2015, countries adopted a set of Sustainable Development Goals (SDGs), which include commitments to end hunger, achieve food security, and improve nutrition by 2030. To contribute to the achievement of these goals, the UN Decade of Action on Nutrition was proclaimed by the United Nations General Assembly in April 2016, setting a revolutionary shift in the fight against malnutrition in all its forms. This short paper examines how policies affecting trade and markets are a means to achieve the Decade’s broader nutrition objectives.